The inscription: thirty years after. Who will be able to defend it? - Ortiz Pasco, Jorge (2014)
One of the most important figures of Registry Law is the inscription: The reason for theregistration procedure. It seeks, through it,to grant legal protection to the owner of the registration, by the registration publicity itbrings.In this article, the author analyzes thisimportant legal figure, by focusing on the article 2013 of the Peruvian Civil Code, whichhe considers must be renovated and updated, according to the circumstances and recent regulatory changes.